Knowledge , Attitude, and Perception of Family Members regarding the Effects of Anaesthesia on Down Syndrome Patients in Benghazi - A Alshami, hiba; S E Hussein , Maryam; AlShafei , Ghada; Rizk , Hadeel; A. Elmsmary , Ainor; Al Shareef , Dareen; Samer , Hadeel; Ibrahim , Nour; Khaled , Wafaa (Libyan Journal of Medical and Applied Sciences, 2026)
Down syndrome (DS) is the most common chromosomal abnormality, associated with unique anatomical and physiological challenges that increase the risk of complications during anaesthesia. Family members, particularly parents, play a critical role in the perioperative care and decision-making process for these patients. However, their level of awareness and perception regarding anaesthetic risks remains under-researched in Libya. This study aimed to assess the knowledge, attitudes, and perceptions of family members in Benghazi regarding the risks and effects of anaesthesia on patients with Down syndrome. A descriptive cross-sectional study was conducted in Benghazi, Libya, targeting family members of patients with Down syndrome attending the Benghazi Medical Center (BMC) and various rehabilitation centers. Data were collected using a pre-validated questionnaire distributed between November and December 2025. A total of 54 family members participated in the study. The majority of respondents were mothers (66.7%) and parents (81.5%) of the patients. The study revealed a significant communication gap; 72.2% of participants reported that they were not informed about specific anaesthetic risks by healthcare providers, and 53.7% stated they did not understand the information provided. Despite this, a high percentage (81.5%) demonstrated awareness that DS patients face increased anaesthetic risks compared to the general population. Anxiety levels were high, with 55.6% of family members reporting being "extremely anxious" about the procedures. Furthermore, 92.6% of respondents believed that healthcare providers require additional specialized training to manage these patients safely. Family members of Down syndrome patients in Benghazi exhibit a high level of vigilance and concern regarding anaesthetic safety but face significant gaps in effective communication from healthcare teams. While families are aware of the heightened risks, their anxiety is exacerbated by a lack of clear information. There is an urgent need to establish structured preoperative communication protocols and educational programs to support families and ensure informed decision-making.